Type B congenital pyloric atresia: a case report - Singh, Dikshant; Kumar, T. Seetam; Sen, Jyotsna (International Journal of Research in Medical Sciences, 2020)
This is a case of congenital pyloric atresia type B not associated with any other anomaly rare condition, seen as an isolated anomaly with excellent prognosis) of two days female child presenting with vomiting since birth. X-ray abdomen showed only stomach air bubble, sonography showed distended stomach with echoes and on barium meal no passage of contrast was seen beyond pyloric antrum even after 24 hours. Patient underwent Heineke-Mikulicz pyloroplasty and postoperative recovery was uneventful.